The Impact of Use of Google Workspace for Education on Student Engagement in Sustainability Accounting Learning - Nurkhin, Ahmad; Fachrurrozie, Fachrurrozie; Muhsin, Muhsin; Widiyanto, Widiyanto; Santoso, Jarot Tri Bowo; Harsono, Harsono (Universitas Negeri Semarang, 2023)
This study aimed to describe the use of Google workspace for education and explain its effect on student engagement in sustainability accounting learning. Descriptive quantitative research was intended to describe lecturers' experiences in using the Google platform to increase student engagement. In addition, this study used causality analysis to present empirical evidence of the effect of using Google workspace for education on student engagement. The research respondents were students participating in the Sustainability Accounting course at the Faculty of Economics and Business, Universitas Negeri Semarang in the even semester of 2022/2023. The research variable was the use of Google Workspace for Education, teaching behavior, and student engagement. Utilization rate was measured by the frequency of using Google features during sustainability accounting learning. Student engagement was measured by the constructs of agentic engagement, behavioral engagement, emotional engagement, and cognitive engagement. Data collection methods used questionnaires and observation. The data analysis method used quantitative descriptive analysis and multiple linear regression analysis. The results of the study showed that the use of Google workspace for education that could be applied in sustainability accounting learning was (1) the use of Google Drives, Google Forms, and Google Scholar features in project-based sustainability accounting learning, and (2) the use of Google Docs, Jamboard and YouTube applications for learning in class interactively. Empirical evidence indicated that the use of Google workspace for education could not significantly increase student engagement. In addition, teaching behavior was proven as predictor of student engagement significantly.